The Effect of Fertilization Combination and Paclobutrazol Concentrations on the Productivity of Rice Plants (Oryza sativa L.) - Fitrianti Rahmawati; Agus Sulistyono; Pangesti Nugrahani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Rice (Oryza sativa L.) is a key agricultural commodity and represents the primary carbohydrate source for the Indonesian population. Despite its importance, national rice productivity is still relatively low compared to other major rice-producing countries. This study aimed to evaluate the most suitable combination of paclobutrazol concentration and N, P, K fertilization to optimize rice growth and yield performance. The research was conducted from December 2024 to February 2025 in Ngraho Village, Bojonegoro Regency, East Java. A Split Plot Design was employed, involving two factors: paclobutrazol concentration as the subplot factor and fertilizer combination as the main plot factor. In total, 16 treatment combinations were arranged with three replications, resulting in 48 experimental units. The best performance was obtained from the combination of Urea (600 kg/ha), SP36 (300 kg/ha), KCl (200 kg/ha), and paclobutrazol at 600 ppm, which improved multiple growth and yield parameters. The treatment showed statistically significant effects and is recommended for implementation in rice cultivation under similar agroclimatic environments. Further investigations in different regions and planting periods are necessary to assess the stability of these outcomes.